A Clinical And Pharmacogenetic Investigation Of Methadone Maintenance Therapy (MMT) In Opiate Dependent Individuals - Mohamad, Nasir (2011)
Over time, many discoveries revolutionized medicine. Methadone has revolutionized the management of opiate dependence. With MMT, most patients respond well and their health improves. Its complex pharmacology and “opiophobia” however impede its full usefulness. Among the “opiophobics”, alternative therapies with, as an example, Chinese medicines, are frequently sought and advocated. We performed a laboratory and clinical study with the objective of investigating factors that predict successful MMT program, in an effort to improve therapy with methadone and to help us develop guidelines on the optimization of MMT. We also studied the effect of a Chinese herb, BioLitrin in patients maintained on MMT to evaluate its role as an adjunct to MMT.